Maintenance management of public building Majlis Perbandaran Kota Bharu (MPKB) / Nor Ayunie Amran - Amran, Nor Ayunie (Faculty of Architecture, Planning and Surveying, 2009)
Maintenance management is an important aspect in building or property, this management can be listed as a planning, controlling, co-ordinating, and motivating process of maintenance works. This aspect is to make sure the maintenance management can achieve the purpose of maintenance in maintenance definition. The BS3811: 1984 defined ‘a combination of any actions carried out to retain an item in, or restore it to an acceptable condition’. Maintenance is one of important activity for all building includes public building. Public building is property which owned by a government or community, the maintenance programme for public building will be managed by their own state government methods such as their own department of maintenance management or others outside contractors. In maintenance management, it has a proper programme and strategy to create a good management. This programme and strategy is to solve problem occur in maintenance management such as overstaff in organization, over budget of costing and the schedule of maintenance work.